Urgent percutaneous coronary intervention in type 2 Wellens’ syndrome: A case report of an atypical presentation in an elderly patient - Thierno Hamidou Diallo; Raynatou Djafarou Boubacar; Illy Sawssen Azday; Rokya Fellat; Nadia Fellat (SAGE Open Medical Case Reports)
Traditionally reflecting critical stenosis of the proximal left anterior descending (LAD) artery, Wellens’ syndrome (WS) is an electrocardiogram (ECG) pattern of biphasic or deeply inverted T waves in leads V2 and V3. This critical stenosis can progress to an extensive anterior myocardial infarction (MI) if early and appropriate management is not received promptly. The diagnosis of severe stenosis of the LAD coronary artery can be made by using electrocardiographic changes in Wellens’ syndrome. Due to the significant area that the LAD vascularizes, patients who exhibit symptoms and test results suggestive of this syndrome should be referred right away for an angiographic exploration in order to confirm the diagnosis and guide treatment. We report a case of a 71-year-old male admitted to our department for acute chest pain. His ECG showed Wellens’ syndrome type 2 during both chest pain and pain free with slightly elevated troponin. His TIMI score was 3 and the GRACE score was 136. Critical stenosis of the LAD coronary artery was found in the coronary angiography, which required a drug-eluting stent. The patient was discharged asymptomatic from medical therapy. The diagnosis was established on the basis of the patient’s interview, ECG analysis, and coronary angiography.